Hegemony in the digital age : the Arab/Israeli conflict online - Marmura, Stephen M. E., 1965- (Critical media studies., 2010)
Internet technology has arguably changed the rules by which individuals, social movements, and institutions compete for political and cultural influence in technologically advanced societies. The author considers this reality through reference to the concept of hegemony; looking to the ways in which diverse actors in American civil society compete with one another while simultaneously challenging dominant sources of authority. The Arab/Israeli conflict is drawn upon as a boundary object holding direct interest to a wide range of state-aligned lobbies, broadly-based social movements, and margin.